Empirical Study on MSME Compliance with SAK ETAP in Boyolali City - Hapsari, Rosita Dwi; Huda, Haris Ihsanil; Ratnaningrum, Ratnaningrum (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the factors influencing the compliance of Micro, Small, and Medium Enterprises (MSMEs) with the application of Financial Accounting Standards for Entities Without Public Accountability (SAK-ETAP) in Boyolali City. The background of this research lies in the low awareness and capability of MSME owners in preparing financial statements based on accounting standards, which may affect business management and access to financing. The variables examined include educational background, business age, and socialization or training received by MSME owners. This research employed a quantitative approach with a survey method conducted on 100 MSME respondents across three districts in Boyolali City. Data were analyzed using multiple linear regression. The results reveal that educational background, business age, and socialization positively and significantly affect MSME compliance with SAK-ETAP implementation. Simultaneously, these three variables contribute 80.8% to the application of SAK-ETAP. The findings highlight the importance of enhancing competencies through formal education and training, business experience, and government support in the form of socialization and assistance, enabling MSMEs to prepare financial reports in accordance with accounting standards. Therefore, implementing SAK-ETAP can promote transparency, increase business credibility, and strengthen the sustainability of MSMEs in Boyolali City.